An ethical exploration of the narratives surrounding substance use and pain management at the end of life: a discussion paper. (August 2020) - Witham, Gary; Yarwood, Gemma; Wright, Sam; Galvani, Sarah
This discussion article examines narrative positioning related to pain management for people who use substances at the end of life. We explore how dominant narrative genres associated with biomedicine, such as 'restitution' and narratives common within the context of drug services such as 'recovery' can hinder effective pain management within this population. We argue that these discourses can marginalise the ethical self-identity of patients who use substances at the end of life. It can also trouble health and social care professionals in supporting patients and generating counter-narratives that challenge those often associated with substance use. Stigma is a common experience for this population with stereotyping as 'junkies' and associated with criminality. They are positioned as drug-seeking, and this requires more surveillance at the end of life when opioid therapy is potentially more available and authorised. This can make it challenging to generate 'companion' stories that are positive and maintain moral adequacy. Dominant biomedical narrative genres often prevent the recognition of the fractured stories that people using substances can often present with. This can lead to narrative silencing and to the under treatment of pain. The person's self-identity is invested in narratives of recovery, and opioid use symbolises their addicted past because for practitioners, this population is at clinical risk with the potential for drug seeking behaviours. Whilst not requiring formal ethical review this discussion paper was constructed in accordance with good scientific practice with the work of other researchers respected and cited appropriately.